Biomechanical comparison of three perceived effort set shots in team handball players - Plummer, H. A.; Gascon, S. S.; Oliver, G. D. (The Journal of Strength and Conditioning Research, 2017)
Shoulder injuries are prevalent in the sport of team handball; however, no guidelines currently exist in the implementation of an interval throwing protocol for players returning from an upper extremity injury. These guidelines exist for the sport of baseball, but team handball may present additional challenges due to greater ball mass that must be accounted for. The purpose of this study was to examine kinematic differences in the team handball set shot at 50, 75, and 100% effort which are common throwing intensities in throwing protocols. Eleven male team handball players (23.09 ± 3.05 years; 185.12 ± 8.33 cm; 89.65 ± 12.17 kg) volunteered. An electromagnetic tracking system was used to collect kinematic data at the pelvis, trunk, scapula, and shoulder. Kinematic differences at the shoulder, trunk, and pelvis were observed across effort levels throughout the set shot with most occurring at ball release and maximum internal rotation. Significant differences in ball speed were observed between all 3 effort level shots (p < 0.001). Team handball players are able to gauge the effort at which they shoot; however, it cannot be assumed that these speeds will be at a certain percentage of their maximum. The results of this study provide valuable evidence that can be used to prepare a team handball player to return to throwing activities.